PENGARUH KUALITAS LAYANAN, HARGA, DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI LOGAM MULIA PADA PT PEGADAIAN PERSERO CP BARRU - Lestari Daswan; Osman Lewangka; Djumidah Maming (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This study aims to determine the Effect of Service Quality, Price, and Trust in Purchasing Decisions Through Interest in Buying Precious Metals at PT Pegadaian Persero CP Barru. The research method used is quantitative research using the survey method. The population in this study was active customers from 2017-2018 who bought precious metals at PT Pegadaian Persero CP Barru. The samples taken in this study were 77 respondents in 3 locations precisely at UPC Palanro, UPC Mangkoso, and UPC Takkalasi. Data collection in this study uses questionnaires, literature studies, and observations. Data analysis techniques use descriptive data analysis techniques hypothesis testing. The results of this study indicate that the results of this study indicate that service quality, price, trust, service quality, price, and trust, have a positive and significant effect on buying interest. The indirect effect of service quality on purchasing decisions through buying interest is smaller than the direct effect of service quality on purchasing decisions. The indirect effect between prices on purchasing decisions through buying interest is smaller than the direct effect of prices on purchasing decisions. The indirect effect between trust in purchasing decisions through buying interest is smaller than the direct influence of trust in purchasing decisions.